Pengembangan Asesmen Berbasis Game Education “Smart Pirates” pada Materi Tekanan Hidrostatis - Choirun Nisah Alifiyah; Magfira Cindy Dianningrum; Bakhrul Rizky Kurniawan; Cahyani Intan Ramadani (-)
This paper consist of research and development of assessment based on game education “Smart Pirates” to facilitate educators in assessing the material of Hydrostatic Pressure and create a fun learning atmosphere for students. The research has been conducted using a research and development theory adapted from Borg and Gall design and consisted of three stages. The research subjects were students of FMIPA UM. The instrument used was a questionnaire and quantitative descriptive data analysis. Based on the results of this research, it can be concluded that the assessment developed has met the eligible criteria. "Smart Pirates" can help educators in making assessments effectively and optimally and make students relax in working on the questions well.